Novel methodology for measuring intraoral wear in enamel and dental restorative materials. Issue 6 (21st September 2020) - F. Esquivel‐Upshaw, Josephine; Hsu, Shu‐Min; Bohórquez, Ana C.; Abdulhameed, Nader; Scheiffele, Gary W.; Kim, Mijin; Neal, Dan; Chai, John; Ren, Fan
Abstract: Objectives: To test the hypotheses that (a) the chairside/handheld dental scanner combined with a metrology software will measure clinical wear in vivo in agreement with measurements from X‐ray computed microtomography and; (b) polished monolithic zirconia does not cause accelerated wear of opposing enamel. Materials and methods: Thirty single crowns were randomized to receive a monolithic zirconia or metal‐ceramic crown. Two non‐restored opposing teeth in the same quadrants were identified to serve as enamel controls. After cementation, quadrants were scanned using an intraoral dental scanner. Patients were recalled at 6‐months and 1‐year for re‐scanning. Scanned images were compared using a metrology software to determine maximum vertical wear of teeth. The accuracy of the scanning measurements from this new method was compared with X‐ray computed microtomography (micro‐CT) measurements. Statistical analysis was performed using Mann–Whitney U test to determine significant differences between wear of enamel against zirconia, metal‐ceramic or enamel. Linear regression analysis determined agreement between measurements obtained using intraoral scanning and micro‐CT. Results: Regression analysis demonstrated that there is a quantitative agreement between depth and volume measurements produced using intraoral scanning and the micro‐CT methodologies. There was no significant difference between the wear of enamel against polished monolithic zirconia crowns and enamel against enamel. Conclusions: Intraoral scanning combined with a matching software can accurately quantify clinical wear to verify that monolithic zirconia exhibited comparable wear of enamel compared with metal‐ceramic crowns and control enamel. Agreement between the intraoral scanner and the micro‐CT was 99.8%. Clinical Trials.gov NCT02289781.